Powder for solid electrolytes and lithium secondary batteries using the same
Patent Information
- Application Number
- JP2025062223
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
AI Technical Summary
【0025】 本発明の固体電解質用粉末によれば、Taのようなレアメタルを含めずに、リチウム二次電池に適した固体電解質を得ることができる。しかも、特に、焼結助剤等を用いなくても、固体電解質を得る際の焼結温度を実効的に低温化することができ、イオン伝導性に優れて、相対密度の高い固体電解質を得ることが可能になる。
Smart Images

Figure 2026168795000004 
Figure 2026168795000005 
Figure 2026168795000006
Abstract
Description
[Technical Field]
[0001] The present invention relates to a powder for solid electrolytes that can be obtained by sintering, and to a lithium secondary battery using the same. More specifically, it relates to a powder for solid electrolytes consisting of a composite oxide having a Li-Al-La-Zr-Bi-O garnet-type structure, and to a lithium secondary battery using the same. [Background technology]
[0002] Composite oxides with a garnet-type structure, which are lithium-ion conductors, are attracting attention as materials for lithium-ion secondary batteries.
[0003] This composite oxide has a basic composition of Li7La3Zr2O 12 Because it can be represented as such, it is generally called an LLZ material.
[0004] Here, LLZ-type materials exist in tetragonal or cubic crystal structures, but the cubic phase, in particular, can increase ionic conductivity. Therefore, composite oxides with a cubic garnet-type structure that have good ionic conductivity and excellent reduction resistance are considered promising as solid electrolytes used in lithium secondary batteries.
[0005] One known method for obtaining cubic LLZ-type materials is to substitute some of the constituent elements of the LLZ-type material with other elements. It is also known that a cubic phase exhibiting higher ionic conductivity can be obtained by sintering the LLZ-type material through heat treatment at a high temperature of around 1200°C.
[0006] Thus, in order to stabilize the cubic phase and densify the resulting electrolyte, LLZ-based materials are heat-treated at high temperatures and sintered. However, this heat treatment may cause lithium to volatilize. Furthermore, when forming electrodes, electrode active materials may be mixed in and sintered, but high-temperature heat treatment can cause the LLZ-based material to react with the electrode active materials, forming an impurity phase, which can be a problem.
[0007] For example, a raw material powder containing Li, La, Zr, and Bi is known that can give a cubic garnet-type crystal structure in which some of the Zr sites are substituted with Ta or Bi (see Patent Document 1). Patent Document 1 states that by having 5 to 30 mol% of Zr sites substituted with Ta or Bi in 100 mol%, a crystal structure exhibiting the desired ionic conductivity can be obtained more reliably, and when sintering to obtain an oxide sintered body, sintering can be completed at a lower temperature and in a shorter time.
[0008] Furthermore, there is a known material that contains Li, La, Zr, and Bi, and in which a cubic garnet-type solid electrolyte can be obtained in which a portion of the La sites are substituted with Bi (see Patent Document 2). Patent Document 2 states that by having a Bi substitution amount of 1 to 20 mol% of La per 100 mol%, a crystal structure that exhibits the desired ionic conductivity can be obtained more reliably, and when sintering this material to make a solid electrolyte, it becomes possible to complete the sintering process at a lower temperature and in a shorter time.
[0009] However, in these Patent Documents 1 and 2, the sintering temperature used to obtain the oxide sintered body in the examples is 1030-1050°C in Patent Document 1 and 1000-1100°C in Patent Document 2, neither of which is sufficient to actually lower the heat treatment temperature.
[0010] On the other hand, there is a known material that has solid electrolyte particles and a non-molten phase, wherein the solid electrolyte particles are composed of a lithium lanthanum zirconium-based composite oxide having a garnet-type crystal structure and containing an M3 element consisting of at least one of Bi and Sb, and the non-molten phase is composed of a material having a lower lithium ion conductivity than the lithium lanthanum zirconium-based composite oxide (see Patent Document 3).
[0011] In this Patent Document 3, it is stated that by allowing the non-molten phase to be present in at least one of the interior of the solid electrolyte particles and between the particles to partially increase the defect concentration, hopping of lithium ions is consequently facilitated, and the lithium ion conductivity is improved. In addition, since the lithium lanthanum zirconium-based composite oxide constituting the solid electrolyte particles contains the M3 element consisting of at least one of Bi and Sb, the density can be easily increased even by low-temperature sintering at less than 900°C, which can contribute to the increase of the interfaces between the solid electrolyte particles. Therefore, it is stated that the obtained solid electrolyte can achieve high lithium ion conductivity even by low-temperature sintering at less than 900°C.
[0012] Further, when a garnet-type solid electrolyte is used as a positive electrode layer, there is a known structure that includes a first phase composed of a positive electrode active material containing Li, a second phase composed of a garnet-type solid electrolyte containing Li, Bi, M2 (M2 is one or more selected from the group consisting of Ca, Sr, Ba, Mg, Y and Rb) and O, and a third phase composed of a Li-Bi-M2-O-based compound that is different from the first phase and the second phase and is composed of a compound containing Li, Bi, M2 (the same as above) and O (see Patent Document 4).
[0013] In this Patent Document 4, it is stated that during the production of the positive electrode layer for an all-solid-state battery, sintering is promoted because the Li-Bi-M2-O-based compound contained in the third phase is generated from part of the solid electrolyte that is the second phase at a relatively low sintering temperature of less than 900°C.
[0014] However, as can be seen from the content of the examples in the aforementioned Patent Document 3, in practice, in all samples (Samples 3C, 4C, Samples 1 to 28) except for some samples (Samples 1C and 2C), at least one of the non-molten phase Li₂ZrO₃ and the sintering aids Li₇SbO₆ and Li₃BO₃ is used. In addition, for Samples 1C and 2C that do not use these, the resulting solid electrolyte has a lower relative density. Similarly, in Patent Document 4, in its examples, the sintering aid Li₃BO₃ is used in all samples (Samples 2 to 34) except for a part (Sample 1). For Sample 1 that does not use the sintering aid, the resulting solid electrolyte has a lower relative density compared to those using the sintering aid.
[0015] Furthermore, it is an LLZ-based material using Ta, namely Li₆La₃ZrTaO 12 in which it has been reported that the heat treatment temperature required for sintering can be lowered by using Bi as a substitution element (see Non-Patent Document 1). Specifically, it describes that a solid electrolyte can be obtained by heat treatment at 775 to 950°C for 15 hours.
[0016] Note that there is a description that when an oxide composed of Li, La, Zr, and O was produced, TG-DTA measurement was performed on the mixture of the respective raw materials that are the calcination precursors, and it was confirmed that an endothermic peak appears at 725°C (see Non-Patent Document 2). Here, this endothermic peak is explained to be derived from the melting and decomposition of lithium carbonate (Li₂CO₃) contained in the calcination precursor. However, there is no example of performing TG-DTA measurement on the LLZ-based material after calcination. In addition, there is a document describing that lithium carbonate partially exists on the surface of a solid electrolyte having a garnet-type crystal structure containing Li, La, Zr and O (see Patent Document 5). As described in this Patent Document 5, lithium carbonate is generated by the reaction of the solid electrolyte with moisture and carbon dioxide in the atmosphere, and lithium carbonate has a significantly lower lithium ion conductivity than that of the solid electrolyte, and is considered to be a resistive phase. [Prior Art Documents] [Patent Documents]
[0017] [Patent Document 1] Patent No. 6272229 [Patent Document 2] Patent No. 6260250 [Patent Document 3] Japanese Patent Publication No. 2023-16639 [Patent Document 4] Japanese Patent Publication No. 2022-07870 [Patent Document 5] International Publication No. 2024 / 166502 [Non-patent literature]
[0018] [Non-Patent Document 1] Journal of the Ceramic Society of Japan 130 [7] 416-423 2022 [Non-Patent Document 2] International Journal of energy research 2019 43 141-149 [Overview of the project] [Problems that the invention aims to solve]
[0019] As mentioned above, when obtaining solid electrolytes used in lithium secondary batteries, composite oxides having a cubic garnet-type structure are promising, and it is required to keep the heat treatment temperature for sintering them into solid electrolytes as low as possible. In addition to ease of control for obtaining solid electrolytes, it is desirable that the composite oxide can be manufactured using only the composite oxide itself, without using sintering aids as much as possible, in order to ensure uniformity within the sintered body and improve the reproducibility of the obtained sintered body, for example, when obtaining a solid electrolyte sheet as a sintered body.
[0020] From this perspective, we can focus on the method described in Non-Patent Document 1 mentioned earlier, but this method requires the use of Ta, one of the rare metals. Therefore, further improvements are needed to reduce costs.
[0021] Therefore, the inventors diligently studied to solve the above problems and found that by using Al together with Bi and controlling the ratio of Li and La within a specific range, a solid electrolyte with excellent ionic conductivity and increased relative density can be obtained, thus completing the present invention.
[0022] Therefore, the object of the present invention is to provide a powder for solid electrolytes that exhibits excellent ionic conductivity and can also produce a denser solid electrolyte.
[0023] Another object of the present invention is to provide a lithium secondary battery that uses a solid electrolyte obtained by sintering the above-mentioned solid electrolyte powder. [Means for solving the problem]
[0024] In other words, the gist of the present invention is as follows: [1] A powder for solid electrolytes comprising a composite oxide having a garnet-type crystal structure composed of the elements Li, Al, La, Zr, Bi, and O, General formula: Li (7-3A-B)X Al A La 3Y Zr 2-B Bi B O 12 A powder for solid electrolytes that can be expressed as such, and in the above general formula, A, B, X, and Y, which represent the molar ratios of the constituent elements, satisfy the following formulas (1) to (4). 0 <A<0.30···(1) 0 <B<1.00···(2) 0.96 ≤ X ≤ 1.02 ···(3) 0.87 <Y<0.93···(4) [2] When the maximum DTA value between 600 and 660°C by TG-DTA measurement is defined as D1 (μV / mg), and the average DTA value between 660 and 690°C by TG-DTA measurement is defined as D2 (μV / mg), the difference (D1-D2) between D1 and D2 is 3.0×10 -2 μV / mg or more, and when the minimum DTA value between 690 and 720°C by TG-DTA measurement is defined as D3 (μV / mg), the difference (D2-D3) between D2 and D3 is 4.0×10 -2 μV / mg or more, the powder for solid electrolyte according to [1]. [3] The powder for solid electrolyte according to [1] or [2], wherein in the results of powder X-ray diffraction measurement using a CuKα radiation source, the proportion of the tetragonal garnet-type structure relative to the cubic garnet-type structure is 10 mass% or less. [4] The powder for solid electrolyte according to [1] or [2], wherein the primary particle diameter is 5 μm or less. [5] A lithium secondary battery characterized by using a solid electrolyte obtained by sintering the powder for solid electrolyte according to [1] or [2]. [6] A lithium secondary battery characterized by using a solid electrolyte obtained by sintering the powder for solid electrolyte according to [1] or [2] in a separator layer present between a positive electrode and a negative electrode. [Effects of the Invention]
[0025] According to the powder for solid electrolyte of the present invention, a solid electrolyte suitable for lithium secondary batteries can be obtained without containing rare metals such as Ta. Furthermore, particularly without using a sintering aid or the like, the sintering temperature for obtaining the solid electrolyte can be effectively lowered, making it possible to obtain a solid electrolyte with excellent ion conductivity and high relative density. [Brief Description of the Drawings]
[0026] [Figure 1] Figure 1 is a phase diagram of ZrO₂-Li₂O. [Figure 2] Figure 2 is a phase diagram of Bi₂O₃-Li₂O. [Figure 3] Figure 3 shows the XRD measurement results of the powder for solid electrolyte obtained in Example 1. [Figure 4] Figure 4 shows an SEM image of the solid electrolyte powder obtained in Example 1. [Figure 5] Figure 5 shows the results of TG-DTA measurement of the solid electrolyte powders according to Examples 1 and 2. [Figure 6] Figure 6 shows the results of TG-DTA measurements of solid electrolyte powders related to Comparative Examples 1 and 3. [Modes for carrying out the invention]
[0027] The present invention will be described in detail below. The powder for solid electrolytes in the present invention can be used to obtain a solid electrolyte by sintering, and can be represented by the following general formula. General formula: Li (7-3A-B)X Al A La 3Y Zr 2-B Bi B O 12 Here, A, B, X, and Y, which represent the molar ratios of the constituent elements, satisfy the following relationships (1) to (4). 0 <A<0.30···(1) 0 <B<1.00···(2) 0.96 ≤ X ≤ 1.02 ···(3) 0.87 <Y<0.93···(4)
[0028] In other words, the solid electrolyte powder of the present invention consists of a Li-Al-La-Zr-Bi-O composite oxide, in which some of the elements constituting the LLZ system material are substituted with Al and Bi elements. 4+ Position Bi 5+ By performing equivarial substitution, Li + It decreases. Also, Li + Position Al 3+ By substituting with, Al 3+ Li + This reduces Li by three times. + A void is formed at the position. In addition, in this invention, La 3+By reducing (making Y, which represents the molar ratio in the above general formula, less than 1.00) or increasing Li (similarly making X, which also represents the molar ratio, greater than or equal to 1.00), Li-Zr-Bi-O becomes excess, and a phase other than the garnet-type structure is created. In this case, since the lower limit of X (greater than or equal to 0.96) is greater than the upper limit of Y (less than 0.93) which represents the molar ratio in the above general formula, this difference in molar ratio (XY) also becomes an excess of Li. The excess Li-Zr-Bi-O forms a eutectic point, and as will be described later, a liquid phase is formed during calcination at 600-800°C when obtaining the powder for solid electrolytes according to the present invention. As a result, grain growth is suppressed, and the powder is obtained as fine particles.
[0029] Furthermore, when obtaining a solid electrolyte by sintering the powder for solid electrolytes according to the present invention, the Li-Zr-Bi-O contained in the solid electrolyte powder forms a liquid phase, resulting in a high-density product. Incidentally, the liquid phase component Li-Zr-Bi-O that forms the liquid phase is thought to exist around particles having a garnet-type structure when it returns to room temperature. Its form can be crystalline or amorphous, but there is no particular limitation, and either is acceptable.
[0030] In the solid electrolyte powder of the present invention, first, Al 3+ For A, which indicates the substitution amount, its lower limit should be greater than 0, preferably 0.03 or more, and more preferably 0.05 or more. The Li position in LLZ material is Al 3+ By substituting with, the cubic garnet-type structure is stabilized. Incidentally, in the aforementioned Non-Patent Document 1, Ta is used to substitute the Zr position, but no substitution of the Li position with any element other than Li is made. Also, Al 3+ The upper limit of A, which indicates the amount of substitution, is less than 0.30. When A is 0.30, the Li composition is around 5.8, but if the Li composition falls significantly below 6.0, the ionic conductivity decreases. Therefore, the upper limit of A is less than 0.30, preferably 0.20 or less, and more preferably 0.15 or less. Note that Al 3+ Substitution may inhibit Li diffusion, but Al3+ is Li + Because its ionic radius is smaller than that of other ions, and because Li diffusion in a garnet-type structure occurs three-dimensionally, it is thought that the presence of other ions in some parts does not actually have a significant effect on Li diffusion (conductivity).
[0031] Also, Bi 5+ Regarding B, which indicates the amount of substitution, its lower limit should be greater than 0, preferably 0.10 or more, and more preferably 0.20 or more. The upper limit is less than 1.00. If B is 1.00, it will occupy more than 50% of the Zr positions, and there is a risk that a cubic garnet-type structure will not be formed. Therefore, the upper limit of B is less than 1.00, preferably 0.70 or less, and more preferably 0.50 or less.
[0032] Also, Li + For X, which indicates the adjustment amount, the lower limit should be 0.96 or higher, preferably 0.97 or higher, and more preferably 0.98 or higher. The upper limit is 1.02 or lower. If X exceeds 1.02, excess Li oxide may be generated, which may worsen the sinterability. Preferably, it is 1.01 or lower, and more preferably 1.00 or lower.
[0033] Furthermore, La 3+ Regarding Y, which indicates the amount of adjustment, its lower limit should be greater than 0.87, preferably 0.88 or higher, and more preferably 0.89 or higher. The upper limit is less than 0.93. If Y is 0.93, the eutectic effect decreases, and the sinterability may not improve. Preferably, it is 0.92 or lower, and more preferably 0.91 or lower.
[0034] In this invention, Al 3+ Li deficiency due to substitution or Bi 5+ In addition to Zr deficiency due to substitution, Li + Adjustment amount X and La 3+The stoichiometric composition of the LLZ system material is adjusted by the adjustment amount Y. In particular, the inventors have confirmed that, while satisfying the relationships of equations (1) to (4) described above, the relative density of the solid electrolyte obtained by sintering increases in the limited region satisfied by equations (3) and (4) relating to X and Y, resulting in excellent ionic conductivity.
[0035] Furthermore, in the present invention, by satisfying the relationships of equations (1) to (4), the powder for solid electrolytes can be stabilized to have a cubic garnet-type structure as described above. Preferably, in the results of powder X-ray diffraction measurements using a Cukα source, the ratio of tetragonal garnet-type structures to cubic garnet-type structures is 10% by mass or less. More preferably, this ratio is 5% by mass or less. Here, it is desirable to avoid detecting the tetragonal garnet-type structure as much as possible, but since it is difficult to make it as close to zero as possible when considering the quantitative accuracy during XRD measurement, it can be said that a ratio of 5% by mass or less is substantially the lower limit for the existence of tetragonal garnet-type structures. In addition, the ratio of tetragonal garnet-type structures to cubic garnet-type structures was calculated by performing Rietveld analysis on two phases using crystal data of cubic and tetragonal structures from ICSD (Inorganic Crystal Structure Data), as shown in the examples described later.
[0036] Furthermore, in the present invention, by satisfying the relationships of formulas (1) to (4) described above, a different phase exists that is distinct from the garnet-type structure. In particular, Li-Zr-Bi-O is present in excess, and this Li-Zr-Bi-O forms a eutectic point. Therefore, when obtaining the powder for solid electrolytes according to the present invention, a liquid phase is formed during calcination at 600 to 800°C, suppressing grain growth. Specifically, the powder can be obtained as fine particles with a primary particle diameter of 5 μm or less. The primary particle diameter can be measured according to the method described in the examples.
[0037] Furthermore, it is preferable that the powder for solid electrolytes in the present invention has an endothermic peak in the range of 690°C to less than 720°C in the DTA curve obtained by TG-DTA measurement (thermogravimetric differential thermal analysis). As explained in the prior art, LLZ-based materials may produce lithium carbonate by reacting with moisture and carbon dioxide in the atmosphere. Generally, this lithium carbonate shows an endothermic peak at 720°C in the DTA curve obtained by TG-DTA measurement. However, if the endothermic peak is in the range of 690°C to less than 720°C, as described above, when the powder for solid electrolytes according to the present invention is sintered to obtain a solid electrolyte, it can be considered that the Li-Zr-Bi-O contained in the powder for solid electrolytes forms a liquid phase, and a high-density solid electrolyte can be obtained.
[0038] On the other hand, even if an endothermic peak cannot be clearly identified, if the DTA curve obtained by differential thermal analysis (DTA) shows endothermic behavior, i.e., a downward-convex curve, then the behavior related to melting can be identified. Therefore, it is preferable that the solid electrolyte powder in the present invention satisfies the following conditions when subjected to TG-DTA measurement.
[0039] In other words, when the maximum value of DTA between 600 and 660°C measured by TG-DTA is taken as D1 (μV / mg), and the average value of DTA between 660 and 690°C is taken as D2 (μV / mg), then (i) the difference between D1 and D2 (D1-D2) is 3.0 × 10⁻⁶. -2 (b) The value is ≥ μV / mg, and when the minimum value of DTA between 690 and 720°C measured by TG-DTA is taken as D3 (μV / mg), then (b) the difference between D2 and D3 (D2-D3) is 4.0 × 10 -2 If the concentration is above μV / mg, it can be assumed that when obtaining a solid electrolyte, the Li-Zr-Bi-O as described above will form a liquid phase, resulting in a high-density solid electrolyte.
[0040] The reason for focusing on the relationships between D1-D3 and (a) and (b) is that, as mentioned above, when the powder for the solid electrolyte in the present invention is sintered to form a solid electrolyte, the melting behavior (endothermic, with a downward-convex peak) at temperatures above 600°C is quantified by the DTA curve. Here, using the DTA between 600-660°C as a base, if the DTA between 660-690°C satisfies relationship (a) relative to that base, it suggests melting due to a eutectic of Li and Bi oxide as described above. Furthermore, if the DTA between 690-720°C satisfies relationship (b), it suggests melting originating from a phase similar to lithium carbonate. Here, a phase similar to lithium carbonate is defined as a state in which the melting temperature has decreased due to the presence of other elements. As can be seen from the ZrO2-Li2O phase diagram shown in Figure 1, the presence of zirconium oxide in lithium carbonate causes a eutectic point to occur below 700°C. Furthermore, as can be seen from the phase diagram of Bi2O3-Li2O shown in Figure 2, the presence of bismuth oxide in lithium carbonate similarly generates a eutectic point below 700°C. The complex presence of three or more cations, such as Li and Bi, lithium carbonate and Zr, and Li-Zr-Bi-O, yields a melting effect not previously described. Moreover, it is thought that the solid electrolyte powder according to the present invention undergoes favorable liquid-phase sintering due to both these three-or-more-cation complexes and lithium carbonate, or a phase in a state close to lithium carbonate, or their mutual interaction and complex entanglement, and thus melting due to Li-Zr-Bi-O as described above is inferred. The reason why the endothermic peak originating from lithium carbonate is lower than usual is not yet entirely clear, but it is thought to be due to the influence of the presence of Li-Zr-Bi-O as described above.
[0041] The solid electrolyte powder of the present invention can be used as a solid electrolyte for various applications by utilizing its conductivity and density. For example, it can be used in lithium batteries such as lithium secondary batteries, as well as in materials for various gas sensors such as SOx, NOx, carbon dioxide, and oxygen, and lithium-ion sensor materials. In particular, it can be preferably used as a solid electrolyte in all-solid-state lithium secondary batteries. Furthermore, even in conventional lithium-ion secondary batteries that use an electrolyte, by replacing at least a portion of the liquid electrolyte with the lithium-ion conductive oxide material of the present invention, which is a ceramic material, the use of organic electrolytes can be avoided or suppressed, simplifying the battery structure and simultaneously suppressing side reactions caused by organic electrolytes.
[0042] Furthermore, the powder for solid electrolytes of the present invention is in a state before sintering to become a solid electrolyte, and is a calcined powder obtained by calcination. The method for obtaining such a calcined powder for solid electrolytes according to the present invention is not particularly limited, but examples include gas-phase synthesis methods such as PVD and CVD, solid-phase reaction methods, spray pyrolysis methods, and wet methods such as coprecipitation and sol-gel methods. In particular, the following example of synthesis by a solid-phase reaction method can be shown.
[0043] In other words, the raw materials that can be used are sulfates, oxides, carbonates, hydroxides, nitrates, acetates, oxalates, halides, etc., of the constituent elements. These raw materials are mixed using a planetary mill, bead mill, ball mill, etc.
[0044] Next, the resulting mixture is calcined. The calcination temperature is difficult to specify precisely, as it varies depending on the composition of the mixture, but it is generally between 600°C and 1000°C, preferably between 650°C and 900°C. Similarly, the calcination time is difficult to specify precisely, but it is generally between 5 hours and 20 hours, preferably between 10 hours and 15 hours. Furthermore, there are no particular restrictions on the calcination atmosphere, but it is best to use an atmosphere with an appropriate oxygen partial pressure. Examples include air, nitrogen or argon, or nitrogen or argon with adjusted oxygen partial pressure.
[0045] The powder (calcined powder) obtained in this way can be used as is, or it can be further ground. When grinding, planetary mills, bead mills, ball mills, etc., can be used. The particle size after grinding can be adjusted to an appropriate size according to the application, but generally, it is good to have a D50 (average particle size) of about 0.2 μm to 20 μm. Here, D50 is the particle size (median diameter) at which the cumulative number of particles in the volume-based cumulative distribution of particle size becomes 50%. The particle size of the primary particles is as described above.
[0046] The calcined powder obtained in this manner, i.e., the solid electrolyte powder according to the present invention, can be sintered to form a solid electrolyte, which can preferably be used in a lithium-ion secondary battery. The sintering conditions are not particularly limited, but the sintering temperature is preferably 700°C to 1000°C, and more preferably 800°C to 900°C. The sintering time is preferably 5 hours to 20 hours, and more preferably 10 hours to 15 hours. Furthermore, the calcining atmosphere is preferably an atmospheric atmosphere.
[0047] Furthermore, the solid electrolyte obtained by sintering according to the present invention has an ionic conductivity of 1 × 10⁻¹⁶ at room temperature. -4 S / cm or more, preferably 2 × 10 -4 The density is S / cm or higher. Furthermore, the relative density at room temperature is 90% or higher, preferably 91% or higher. These values are obtained when the sintered body is formed using the method described in the following examples. [Examples]
[0048] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.
[0049] (Examples 1-4, Comparative Examples 1-2) As starting materials, lithium carbonate (Rare Metallic), zirconium oxide (PCS60, manufactured by Shin-Nippon Denko Co., Ltd.), aluminum hydroxide (High Purity Chemicals), lanthanum hydroxide (Aldrich), and bismuth oxide (Fujifilm Wako) were prepared and weighed so that A, B, X, and Y in the following general formula were the values shown in Table 1. General formula: Li (7-3A-B)X Al A La 3Y Zr 2-B Bi B O 12
[0050] The raw materials prepared as described above were mixed and ground in isopropanol at 450 rpm for 15 hours using a planetary ball mill (Fritsch Classic Line P-7), and then dried to recover the raw material mixture, which is the calcination precursor.
[0051] Next, the obtained raw material mixture was calcined in an air atmosphere at 700°C for 15 hours on a heat-resistant container to obtain calcined powder. The calcined powder was then placed in a nylon pot together with zirconia balls, ground in ethanol for 16 hours using a planetary ball mill, and then dried to obtain the solid electrolyte powders for Examples 1-4 and Comparative Examples 1-2.
[0052] The solid electrolyte powder obtained above was subjected to powder X-ray diffraction measurements as follows to determine the mass ratio of the tetragonal garnet-type structure to the cubic garnet-type structure. An X-ray diffractometer manufactured by Rigaku Corporation, MiniFlex, was used. The powder was ground into a crystalline powder using a mortar and pestle, and measurements were taken with a goniot radius of 150 mm, an X-ray source of CuKα rays, a tube voltage of 40 kV, and a tube current of 15 mA. The diffraction angle was set to 2θ = 10 to 80°, the scan speed to 2° / min, and the scan step to 0.01°.
[0053] Based on the obtained X-ray diffraction pattern, if the peak position matched that of the cubic garnet crystal structure (ICSD number 183607), it was determined to be a cubic garnet structure. If the peak position matched that of the tetragonal garnet crystal structure (ICSD number 191528), it was determined to be a tetragonal garnet structure. Two-phase Rietveld analysis was performed using the analysis software PDXL2 (version 2.8.4.0) to calculate the mass ratio of the tetragonal garnet structure to the cubic garnet structure. The results are shown in Table 1. Table 2 shows the crystal structure data for the cubic garnet crystal structure (ICSD number 183607), and Table 3 shows the crystal structure data for the tetragonal garnet crystal structure (ICSD number 191528). Furthermore, Figure 3 shows the results of the XRD measurement of the solid electrolyte powder obtained in Example 1.
[0054] [Table 1]
[0055] [Table 2]
[0056] [Table 3]
[0057] Furthermore, the primary particles of the solid electrolyte powder obtained above were observed using a scanning electron microscope (SEM). The primary particle size is the smallest particle unit in the observed image. In cases where particles are fused together, the primary particle size was defined as the length of the longest diagonal after separation of the fused particles at the fusion surface. The results are shown in Table 1. Figure 4 shows an SEM image of the solid electrolyte powder obtained in Example 1. According to this, many primary particles of about 1-2 μm were observed in the solid electrolyte powder of Example 1, and were described as 3 μm or less in Table 1 above.
[0058] On the other hand, TG-DTA measurements were performed on the solid electrolyte powders obtained in Examples 1 and 2 and Comparative Example 1 using a TG-DTA analyzer (STA-2500, manufactured by Netch Japan Co., Ltd.). 20 mg of each of the above solid electrolyte powders was taken as a sample, placed in an alumina pan, and heated to 900°C at a heating rate of 5°C / min under an atmospheric environment. The differential thermal (DTA) curve obtained was then calculated by taking the maximum value of DTA between 600 and 660°C as D1 (μV / mg) and the average value of DTA between 660 and 690°C as D2 (μV / mg), and determining the difference between D1 and D2 (D1-D2). Furthermore, the minimum value of DTA between 690 and 720°C was taken as D3 (μV / mg), and determining the difference between D2 and D3 (D2-D3). The results are shown in Table 1.
[0059] Next, pellets (sintered bodies) were prepared by sintering the solid electrolyte powders obtained in Examples 1-4 and Comparative Examples 1-2 as follows. Specifically, 0.2 g of each of these solid electrolyte powders was taken, placed in a 10φ mold, and held at 20 MPa for 1 minute to obtain a molded body.
[0060] Next, the molded body obtained above is subjected to cold isostatic processing (CIP) at 260 kgf / cm². 2 After being held at a pressure of 25 MPa for 5 minutes, the material was sintered by holding it in air at 850°C for 15 hours to obtain pellets (sintered bodies).
[0061] The obtained pellets were polished with sandpaper to smooth their surfaces, and then their thickness and diameter (width) were measured to calculate the pellet volume. The mass of the pellets was also determined to calculate their density (relative density). Meanwhile, platinum was deposited on both sides of the pellets to create blocking electrodes, and the ionic conductivity (S / cm) at 25°C was measured. A Bio-Logic VSP-300 was used for the measurement, with frequencies ranging from 7.0 MHz to 0.5 Hz. The ionic conductivity was calculated from the pellet thickness and cross-sectional area, with the diameter of the arc in the Nyquist plot representing the total resistance. These results are shown in Table 1.
[0062] (Comparative Example 3) In obtaining the raw material mixture, the molar ratios in the above general formula were set to A=0, B=0, X=1.00, and Y=1.00. The mixture was then mixed and ground for 24 hours using a rolling ball mill instead of a planetary ball mill, and the raw material mixture was recovered. Furthermore, the calcination process to obtain the calcined powder from the raw material mixture was carried out at 1000°C for 5 hours. In addition, the calcination process was carried out in the same manner as in Examples 1-4 and Comparative Examples 1-2, except that the calcined powder obtained from the raw material mixture was calcined using a dry rolling ball mill instead of a planetary ball mill. This was followed to obtain the solid electrolyte powder according to Comparative Example 3.
[0063] Furthermore, pellets (sintered bodies) were obtained using the obtained solid electrolyte powder in the same manner as in Examples 1-4 and Comparative Examples 1-2. Various evaluations were performed in the same manner as described above, and the results are summarized in Table 1.
[0064] As can be seen from Table 1, by using Al together with Bi, as in the present invention, and controlling the ratio of Li and La within a specific range to create a solid electrolyte powder, it becomes possible to obtain a solid electrolyte with excellent ionic conductivity and high relative density. Figure 5 shows the TG-DTA measurement results for the solid electrolyte powders of Examples 1 and 2, and Figure 6 shows the TG-DTA measurement results for the solid electrolyte powders of Comparative Examples 1 and 3. According to these, the solid electrolyte powders of Examples 1 and 2 suggest melting due to eutectic formation of Li and Bi oxides, as well as melting due to lithium carbonate, as described above, and as a result, it is considered that liquid-phase sintering proceeded favorably. Furthermore, these DTA curves also show the presence of an endothermic peak in the range of 700°C to less than 720°C. Thus, with the solid electrolyte powder of the present invention, the sintering temperature can be lowered without using sintering aids, etc., and a solid electrolyte with high relative density can be obtained, and it can also exhibit excellent lithium ion conductivity. In Comparative Examples 1 to 3, the relative density of the obtained solid electrolytes was low, so ionic conductivity was not measured.
Claims
1. A solid electrolyte powder comprising a composite oxide having a garnet-type crystal structure composed of the elements Li, Al, La, Zr, Bi, and O, General formula: Li (7-3A-B)X Al A La 3Y Zr 2-B Bi B O 12 A powder for solid electrolytes that can be expressed as such, and in the above general formula, A, B, X, and Y, which represent the molar ratios of the constituent elements, satisfy the following formulas (1) to (4). 0<A<0.30...(1) 0<B<1.00...(2) 0.96 ≤ X ≤ 1.02 ... (3) 0.87<Y<0.93...(4)
2. When the maximum value of DTA measured between 600 and 660°C by TG-DTA is defined as D1 (μV / mg), and the average value of DTA between 660 and 690°C is defined as D2 (μV / mg), the difference between D1 and D2 (D1 - D2) is 3.0 × 10⁻¹⁰. -2 The value is μV / mg or higher, and when the minimum value of DTA between 690 and 720°C measured by TG-DTA is taken as D3 (μV / mg), the difference between D2 and D3 (D2-D3) is 4.0 × 10⁻¹⁰. -2 The solid electrolyte powder according to claim 1, wherein the concentration is μV / mg or higher.
3. The powder for solid electrolytes according to claim 1 or 2, wherein, in the results of powder X-ray diffraction measurements using a Cukα source, the ratio of tetragonal garnet-type structures to cubic garnet-type structures is 10% by mass or less.
4. The powder for solid electrolytes according to claim 1 or 2, wherein the particle size of the primary particles is 5 μm or less.
5. A lithium secondary battery characterized by using a solid electrolyte obtained by sintering the solid electrolyte powder described in claim 1 or 2.
6. A lithium secondary battery characterized in that a solid electrolyte obtained by sintering the solid electrolyte powder described in claim 1 or 2 is used in a separator layer located between the positive electrode and the negative electrode.
Citation Information
Patent Citations
package
JP1987060250A
Bit compression circuit
JP1987072229A
Mask
JP2022007870A
Solid electrolyte and lithium ion battery
JP2023016639A
Ion conductor, composite, sheet, electrode, separator, and power storage device
WO2024166502A1